First Impression of Greek University Students on Taking Massive e-Exams due to COVID-19 Pandemic - Ioannis, Paliokas; Alexandros, Tzallas; Konstantinos, Kalafatakis; Nikolaos, Giannakeas (Biology, Engineering, Medicine and Science Reports)
Dear Editor-in-Chief, Previous letters have suggested the implementation of certain measures to either ameliorate the effects of the financial crisis or even modernize the Greek academic institutions over the previous decade (2010-2019), either in general1 or in the context of biomedical education.2 In these letters, the authors proposed a series of predesigned steps to achieve the desired results. What we would like to raise the attention of the readership to, is another driving force of change in the Greek academic sector (other than carefully designed plans): forced adaptation to external circumstances, like to COVID-19 pandemic. Some European countries (like the United Kingdom or Nordic countries) have made serious investments in e-learning platforms and curricula over the last 10-15 years (and thus acclimatized their corresponding academic communities into the concept of e-exams),3 while others, like Greece, are not similarly mature in efficiently (from an organizational, pedagogic and technological point of view) integrating distant learning approaches and e-examinations into their academic curricula.